Monitoring of Indoor Air Quality in a Classroom Combining a Low-Cost Sensor System and Machine Learning - Ioannis D. Apostolopoulos; Eleni Dovrou; Silas Androulakis; Katerina Seitanidi; Maria P. Georgopoulou; Angeliki Matrali; Georgia Argyropoulou; Christos Kaltsonoudis; George Fouskas; Spyros N. Pandis (Chemosensors)
Monitoring indoor air quality in schools is essential, particularly as children are highly vulnerable to air pollution. This study evaluates the performance of the low-cost sensor-based air quality monitoring system ENSENSIA, during a 3-week campaign in an elementary school classroom in Athens, Greece. The system measured PM2.5, CO, NO, NO2, O3, and CO2. High-end instrumentation provided the reference concentrations. The aim was to assess the sensors’ performance in estimating the average day-to-day exposure, capturing temporal variations and the degree of agreement among different sensor units, with particular attention to the impact of machine learning (ML) calibration. Using the factory calibration settings, the CO2 and PM2.5 sensors showed strong inter-unit consistency for hourly averaged values. The other sensors, however, exhibited inter-unit variability, with differences in the reported average day-to-day concentrations ranging from 20% to 160%. ML-based calibration was investigated for the CO, NO, NO2, and O3 sensors using measurements by reference instruments for training and evaluation. Among the eleven ML algorithms tested, the Support Vector Regression performed better for the calibration of the CO, NO2, and O3 sensors. The NO sensor was better calibrated using the Elastic Net algorithm. The inter-unit variability was reduced by a factor of two after the ML calibration. The daily average error compared to the reference measured was also reduced by approximately 15–50% depending upon the sensor.